Low-Income Families, Maternal Labor Supply, and Welfare Reform - Viola Garstenauer; Nawid Siassi (TU Wien, Institute of Statistics and Mathematical Methods in Economics, Research Unit in Economics, 2024)
In this paper, we examine reforms that alleviate large employment disincentives induced by child-related transfers for married mothers. We develop a life-cycle model where married couples face labor market, child care and fertility risk, and make joint labor supply and consumption-saving decisions. The evolution of female human capital is endogenous and shaped by mothers' employment decisions. We calibrate the model to the U.S. using data from the Current Population Survey. We show that participation tax rates exceed 25 percent for most mothers in our sample, and can be as high as 60 percent when including child care expenses. We then evaluate reforms to existing tax credits for working couples. We find that (i) expanding child care tax credits and (ii) introducing a secondary earner EITC deduction lead to substantially higher employment rates among married mothers. Both reforms are easily implementable, self-financing, and welfare-improving. A combination of both reforms closes the maternal employment gap altogether.
Keywords: H24; H31; J12; J22; 330; Family labor supply; Child-related transfers; Income taxation